Perception Of The Effectiveness Of In-House Training Program On Production Supervisors And Operators - Swaminathan, Arunasalam (1998)
This study attempted to identify the effectiveness of in-house training program on two groups of production supervisors and operators from a manufacturing industry with the moderating effects of age, gender, educational level, working experience, marital status, residence and course duration.